Efficiency of encoding schemes in mobile WiMAX - Benes, J.; Prokopec, J. (2011 21st International Conference Radioelektronika, 2011)
Mobile WiMAX (Worldwide Interoperability for Microwave Access) standardized by IEEE 802.16e is a broadband wireless system based on Scalable OFDMA (Orthogonal Frequency Division Multiple Access). This standard is suitable for the last mile connection in areas where it is not possible to build wired infrastructure, nevertheless it provides a broadband connection for nomadic users and supports cellular structure. Its main advantage compared to Wi-Fi standard is the possibility of a very powerful handling of radio resources allocation to users in order to adjust quality of radio-environment and number of active users at given area. This article investigates impact of different encoding schemes used in Mobile WiMAX to theoretical throughput and deals with efficiency evaluation of these schemes.